2021
DOI: 10.1016/j.jcf.2020.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Phages as immunomodulators and their promising use as anti-inflammatory agents in a cftr loss-of-function zebrafish model

Abstract: Cystic Fibrosis (CF), one of the most frequent hereditary disease due to mutations in the CFTR gene, causes mortality in humans mainly due to infection in the respiratory system. However, besides the massive inflammatory response triggered by chronic bacterial infections, a constitutive pro-inflammatory state associated with the most common CFTR mutations has been reported in paediatric cases before the onset of bacterial colonization. In a previous works we isolated and characterized a mix of virulent bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Two-way cooperation exists between phages and the immune system called "Immunophage Synergy", whereby both complement each other towards faster resolution of infections and minimal tissue damage, as seen in neutrophil-phage cooperation, reported by Roach et al (2017) against P. aeruginosa. In a similar study, Cafora et al (2020) showed the anti-inflammatory role of the phage cocktail in terms of reduction of pro-inflammatory markers in P. aeruginosa infection using the zebrafish model. Phage cocktail injections significantly reduced neutrophil migration and heightened proinflammatory cytokine levels highlighting the molecular interaction between phages and the cells of the vertebrate immune system in CF disease and the anti-inflammatory role of phages.…”
Section: Phage Against Pulmonary Pathogens: Attack At Multiple Frontsmentioning
confidence: 87%
“…Two-way cooperation exists between phages and the immune system called "Immunophage Synergy", whereby both complement each other towards faster resolution of infections and minimal tissue damage, as seen in neutrophil-phage cooperation, reported by Roach et al (2017) against P. aeruginosa. In a similar study, Cafora et al (2020) showed the anti-inflammatory role of the phage cocktail in terms of reduction of pro-inflammatory markers in P. aeruginosa infection using the zebrafish model. Phage cocktail injections significantly reduced neutrophil migration and heightened proinflammatory cytokine levels highlighting the molecular interaction between phages and the cells of the vertebrate immune system in CF disease and the anti-inflammatory role of phages.…”
Section: Phage Against Pulmonary Pathogens: Attack At Multiple Frontsmentioning
confidence: 87%
“…Phage therapy, done by injecting a phage cocktail in the yolk sac of PAO1-infected embryos, was shown to reduce lethality, bacterial burden, and the proinflammatory response caused by PAO1 infection at 20 hpi both in wild-type and CF zebrafish ( Cafora et al., 2019 ). In addition, phages alone mitigate inflammation in wild-type and CF zebrafish by reducing the expression levels of proinflammatory cytokines and the neutrophilic recruitment to the infection site ( Cafora et al., 2020a ).…”
Section: Validation Of Anti- Pseudomonas Strategies In Zebrafishmentioning
confidence: 99%
“…To the authors’ knowledge, the only publication measuring the effects of phage on neutrophilic migration was conducted using Wild-type and hyper-inflamed cftr loss-of-function zebrafish embryo models [ 58 ]. Using these, it was determined that a four-phage cocktail had immunomodulatory effects via the downregulation of pro-inflammatory cytokines and reduced neutrophil migration in response to acute inflammatory induction by tailfin amputation [ 58 ].…”
Section: Preclinical Data Generationmentioning
confidence: 99%
“…To the authors’ knowledge, the only publication measuring the effects of phage on neutrophilic migration was conducted using Wild-type and hyper-inflamed cftr loss-of-function zebrafish embryo models [ 58 ]. Using these, it was determined that a four-phage cocktail had immunomodulatory effects via the downregulation of pro-inflammatory cytokines and reduced neutrophil migration in response to acute inflammatory induction by tailfin amputation [ 58 ]. Recently, the development of a transepithelial migration model has enabled researchers to measure polymorphonuclear neutrophilic migration through epithelial monolayers at ALI in response to a stimulus such as purified airway supernatants from CF patients [ 59 ].…”
Section: Preclinical Data Generationmentioning
confidence: 99%
See 1 more Smart Citation